(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
The growing interest in the acquisition of new knowledge about the behavior of materials used in the construction of optoelectronic devices has led to the search for new materials instrumentation and characterization techniques for understanding electronic phenomena associated with optical properties inherent to semiconductor materials. For this reason, an airtight chamber with controlled emission in the UV - visible and near infrared was developed. This chamber was integrated to the impedance analyzer Solartron SI 1260 IMPEDANCE / GAIN - PHASE ANALYZER in order to improve and diversify their operation, thus making this equipment in a system capable of carrying out electric impedance measurements in the presence of different types of optical radiation using electrical photoimpedance spectroscopy technique. Microstructured studies of ZnO films were made at ambient temperature and 120 °C through the system developed. The results indicate a decrease in impedance in one order of magnitude for the films in the presence of UV radiation. This fact was associated with the proximity of this radiation with the gap of 3.17 eV calculated for ZnO microrods. The best results in the saturation and relaxation times of the films were obtained at 120 °C. Thus, it was possible to determine the high efficiency of the ZnO microstructured films as possible UV resistive sensors under high temperature.